INHERITANCE AND GENDER EQUALITY - Yusuf, Muhammad; Wekke, Ismail Suardi (IAIN Ponorogo, 2018)
The format of inheritance rights of sons and daughters, namely 2:1, is based on universal truths in the form of justice with accompanying rights and obligations. The format can be carried out quantitatively if the rights and obligations between sons and daughters go as they should. If there are considerations that guarantee more justice, the numbers can be interpreted qualitatively, namely number 2 (the share of sons) is the maximum number and number 1 (the share of daughters) is the minimum number. Both are aimed at ensuring the realization of maqashid al-syari>'ah in the form of justice. This is also in line with the asitinajang local wisdom (principle of decency)